2011
DOI: 10.1016/j.ajodo.2009.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Moving an incisor across the midline: A treatment alternative in an adolescent patient

Abstract: A 13-year-old sought treatment for a severely compromised maxillary left central incisor and an impacted fully developed left canine. Extraction of both teeth became necessary. As the key component of the revised comprehensive treatment plan, the right maxillary central incisor was moved into the position of the left central incisor. All other maxillary teeth were moved mesially to close any gaps. Active orthodontic treatment was completed after 34 months. Frenectomy, minor periodontal surgeries, and bonded li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
5
15
0
1
Order By: Relevance
“…A recently published case report described treatment in a 13-year-old patient. 7 This is the first report showing the procedure performed in an adult patient. In addition, our case report has the uniqueness of showing the final results of tooth movement across the midpalatal suture documented by means of CBCT.…”
Section: Treatment Resultsmentioning
confidence: 99%
“…A recently published case report described treatment in a 13-year-old patient. 7 This is the first report showing the procedure performed in an adult patient. In addition, our case report has the uniqueness of showing the final results of tooth movement across the midpalatal suture documented by means of CBCT.…”
Section: Treatment Resultsmentioning
confidence: 99%
“…Follin [6] also presented a case report in which a left maxillary incisor was moved into the midline to close the space of right central incisor which was removed due to an odontoma. Other successful orthodontic movements of the maxillary central incisors to the contralateral side were reported in gemination cases [7,9], and dental trauma cases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that the suture bends to accommodate the tooth crossing the midline. 8,13 The maxillary midline was deviated from the facial midline during treatment. Another flaw was the proclination of the mandibular incisors necessitating long-term mandibular retainer wear.…”
Section: Final Evaluation Of Treatmentmentioning
confidence: 99%
“…8,9,13 This case study is the first presenting orthodontic space closure and canine substitution as an option for managing avulsed maxillary central and lateral incisors in a growing patient with a Class I malocclusion. This treatment included moving a central incisor across the midline and substituting a lateral incisor for a central incisor, in combination with canine substitution.…”
Section: Final Evaluation Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation